O vocativo e a interface sintaxe-pragmática no português brasileiro - Juliana Costa Moreira (2013)
This thesis aims to describe and analyze the vocative in the syntactic structure of Brazilian Portuguese BP. In order to obtain evidences about the position of this constituent in the syntactic structure, we considered constructions in which there is cooccurrence of topics, evaluative expressions, interjections, invocations, and we compared some constructions in BP with some examples of European Portuguese EP.This comparison focuses on constructions with the particle sô, reduced form of the vocative senhor in the dialect of Minas Gerais, and the vocative particle pá, reduced form of the vocative rapaz in EP. We used as theoretical framework some hypotheses of the Minimalist Program (Chomsky, 1995), the sentential cartography (Rizzi 1997, 2004), and of the theoretical proposal of Hill (2007) and Hill & Stavrou (2013),according to which, vocatives and interjections are located on a superstructure, in the syntax-pragmatics interface, an area located above CP in a projection SAP (Speech Act Phrase). The basic order of a construction with vocative is one in which this component is located on the left of the sentence. The Portuguese language data shows that thevariation in word order in the constructions with vocative is a result of the movement operations of other constituents that occur in these constructions and the vocative is always in situ. The arrangement of the constituents in these constructions influences the interpretation of the vocative: if it appears in the starting position, it works as a callfunction; if it appears in other positions, it is interpreted as the addressee. According to the analysis of different types of vocatives, we identify in BP that there are different types of interjections: some which express the state of mind of the speaker; and others as the particles of indirect call, that may themselves or together with a vocative works asa way of call. We noticed that the particles of indirectly call are may generally precede a calling and, if an interjection itself precedes a vocative, there will be an addressee and not a call. Therefore, in relation to the hypothesis that the interpretation of the vocativemay vary according to the type of interjection that it precedes, we highlighted a bipartite typology of vocatives and interjections.